Pain in Parkinson disease: mechanistic substrates, main classification systems, and how to make sense out of them$dnarrative review - de Andrade, Daniel Ciampi; Mylius, Veit; Perez-Lloret, Santiago; Cury, Rubens G.; Bannister, Kirsty; Moisset, Xavier; Taricani Kubota, Gabriel; Finnerup, Nanna B.; Bouhassira, Didier; Chaudhuri, Kallol Ray; Graven-Nielsen, Thomas; Treede, Rolf-Detlef (Pain, 2023)
Parkinson disease (PD) affects up to 2% of the general population older than 65 years and is a major cause of functional loss. Chronic pain is a common nonmotor symptom that affects up to 80% of patients with (Pw) PD both in prodromal phases and during the subsequent stages of the disease, negatively affecting patient's quality of life and function. Pain in PwPD is rather heterogeneous and may occur because of different mechanisms. Targeting motor symptoms by dopamine replacement or with neuromodulatory approaches may only partially control PD-related pain. Pain in general has been classified in PwPD according to the motor signs, pain dimensions, or pain subtypes. Recently, a new classification framework focusing on chronic pain was introduced to group different types of PD pains according to mechanistic descriptors: nociceptive, neuropathic, or neither nociceptive nor neuropathic. This is also in line with the International Classification of Disease-11, which acknowledges the possibility of chronic secondary musculoskeletal or nociceptive pain due to disease of the CNS. In this narrative review and opinion article, a group of basic and clinical scientists revise the mechanism of pain in PD and the challenges faced when classifying it as a stepping stone to discuss an integrative view of the current classification approaches and how clinical practice can be influenced by them. Knowledge gaps to be tackled by coming classification and therapeutic efforts are presented, as well as a potential framework to address them in a patient-oriented manner.